PERANCANGAN BILLBOARD TENTANG KESELAMATAN MASYARAKAT DI PINTU PERLINTASAN KERETA API SEBAGAI IKLAN LAYANAN MASYARAKAT DI KOTA PADANG - FEBRINA SARI, Dra. Zubaidah, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Railway is one of the alternative means of transportation in the city of Padang. At railway crossings there are crossroads, intersections, crossings and intersections between roads for trains by public roads. The railway crossing path for road users is the most dangerous location. Frequent accidents and casualties. According to statistical data from PT. KAI Divre II of West Sumatera, from 2013 to 2015 there were 130 accidents, from the number of accidents is the main cause is the road users are negligent in breaking through the railway crossing gate.Public service advertisements (ILM) are required to inform and warn of the danger of passing through railroad crossings to the public. For that it is necessary to design public service ads in the form of billboards. Billboard design is effective and flexible because it has a large size what is described in this billboard high level of legibility by the public. The method used qualitatively with 5W + 1H analysis.The purpose of designing billboards provides regulatory information and safety of riders at the communicative railway.Keywords: Designing, Billboard, Railway.